Complete mitochondrial genome of Lamprotula coreana (Unionidae, Unionoida, Bivalvia). (3rd March 2016) - Lee, Jin Hee; Kim, Sang Ki; Hwang, Ui Wook
Abstract: The complete mitochondrial genome sequence of the Lamprotula coreana, which is an endangered and endemic species in South Korea, was determined. Its length is 15, 819 bp, which mainly consists of 13 protein-coding, 2 rRNA, and 22 tRNA genes. In addition, there were 26 noncoding regions (NC) found throughout the mitogenome of L. coreana, ranging in size from 3 bp to 287 bp.